Mythological narratives: the bold and faithful heroines of the greek novel - Lefteratou, Anna (MythosEikonPoiesis, 2018)
Frontmatter -- Preface and Acknowledgements / Lefteratou, Anna -- Contents -- Introduction -- The bold and virginal: Iphigenia -- The bold and unfaithful: Phaedra -- The bold and the faithful: Penelope and Helen -- Epilogue -- Bibliography -- Index locorum notabiliorum -- Index rerum/nominum notabiliorum